Novel substituted 5‐methyl‐4‐acylaminoisoxazoles as antimitotic agents: Evaluation of selectivity to LNCaP cancer cells. Issue 5 (1st February 2022) - Sadovnikov, Kirill S.; Vasilenko, Dmitry A.; Gracheva, Yulia A.; Zefirov, Nikolay A.; Radchenko, Eugene V.; Palyulin, Vladimir A.; Grishin, Yuri K.; Vasilichin, Vladislav A.; Shtil, Alexander A.; Shevtsov, Pavel N.; Shevtsova, Elena F.; Kuznetsova, Tamara S.; et al.
Abstract: A series of novel antimitotic agents was designed using the replacement of heterocyclic cores in two tubulin‐targeting lead molecules with the acylated 4‐aminoisoxazole moiety. Target compounds were synthesized via heterocyclization of β‐aryl‐substituted vinylketones by tert ‐butyl nitrite in the presence of water as a key step. 4‐Methyl‐ N ‐[5‐methyl‐3‐(3, 4, 5‐trimethoxyphenyl)isoxazol‐4‐yl]benzamide (1aa ) was found to stimulate partial depolymerization of microtubules of human lung carcinoma A549 cells at a high concentration of 100 µM and to totally inhibit cell growth (IC50  = 0.99 µM) and cell viability (IC50  = 0.271 µM) in the nanomolar to submicromolar concentration range. These data provide evidence of the multitarget profile of the cytotoxic action of compound 1aa . The SAR study demonstrated that the 3, 4, 5‐trimethoxyphenyl residue is the key structural parameter determining the efficiency both towards tubulin and other molecular targets. The cytotoxicity of 3‐methyl‐ N ‐[5‐methyl‐3‐(3, 4, 5‐trimethoxyphenyl)isoxazol‐4‐yl]benzamide (1ab ) to the androgen‐sensitive human prostate adenocarcinoma cancer cell line LNCaP (IC50  = 0.301 µM) was approximately one order of magnitude higher than that to the conditionally normal cells lines WI‐26 VA4 (IC50  = 2.26 µM) and human umbilical vein endothelial cells (IC50  = 5.58 µM) and significantly higher than that to primary fibroblasts (IC50  > 75 µM). Abstract : A series of novel 4‐acylaminoisoxazoles was designed and prepared, and their antimitotic activity was evaluated. Compounds 1aa and 1ab were found to stimulate partial depolymerization of microtubules of A549 cells at a concentration of 100 µM, whereas compound 1ab revealed high cytotoxicity to LNCaP cells (IC50  = 0.301 µM) and a significantly better toxicological profile in vitro compared to other synthesized compounds.